2020
DOI: 10.5005/jp-journals-10071-23518
|View full text |Cite
|
Sign up to set email alerts
|

Burnout among Healthcare Workers during COVID-19 Pandemic in India: Results of a Questionnaire-based Survey

Abstract: A bstract Background Burnout, a state of physical and emotional exhaustion, in healthcare workers (HCWs) is a major concern. The prevalence of burnout, due to COVID-19 pandemic in India, is unknown. We therefore conducted this survey. Materials and methods A questionnaire-based survey using Copenhagen Burnout Inventory was carried out among HCWs looking after COVID-19 patients. Questionnaire was sent to the HCWs, using WhatsApp Messenger, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
137
7
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 236 publications
(205 citation statements)
references
References 35 publications
14
137
7
5
Order By: Relevance
“…Descriptive analyses also show that a significant amount of participants (about one out of three) had a high level of emotional exhaustion. This result is in line with the previous literature on the impact of the COVID-19 and other pandemic emergencies on healthcare professional mental health (Barello et al 2020a ; Braquehais et al 2020 ; Giusti et al 2020 ; Kulkarni et al 2020 ; Özdemir and Kerse 2020 ). This is particularly worrying because previous studies have demonstrated that this symptom is associated with a decrease in work performance due to negative behaviors towards work (Wright and Cropanzano 1998 ).…”
Section: Discussionsupporting
confidence: 92%
“…Descriptive analyses also show that a significant amount of participants (about one out of three) had a high level of emotional exhaustion. This result is in line with the previous literature on the impact of the COVID-19 and other pandemic emergencies on healthcare professional mental health (Barello et al 2020a ; Braquehais et al 2020 ; Giusti et al 2020 ; Kulkarni et al 2020 ; Özdemir and Kerse 2020 ). This is particularly worrying because previous studies have demonstrated that this symptom is associated with a decrease in work performance due to negative behaviors towards work (Wright and Cropanzano 1998 ).…”
Section: Discussionsupporting
confidence: 92%
“…The results show that more than half of HCW presented high levels of fatigue and exhaustion related to work (53.1%), personal (52.5%), and client-related burnout (35.4%). These results are substantially higher than those found in the study developed in India with a sample of 2026 HCW [ 46 ], where the prevalence of personal burnout was 44.6% (903) and work-related burnout was 26.9% (544). Compared to the previous report [ 5 ], in the period pre-COVID-19, on 1728 Portuguese HCW, 21.6% showed moderate burnout and 47.8% showed high burnout, the incidence burnout in our study was relatively higher.…”
Section: Discussioncontrasting
confidence: 61%
“…Main characteristics of the 14 studies included in our systematic review are shown in Table 1. Study population included only nurses in five studies, 27,28,33,36,40 while nine studies 2932,34,35,3739 included HCWs in general. A total of 17,390 nurses were included in this systematic review, while two studies 37,38 did not report the number of nurses.…”
Section: Resultsmentioning
confidence: 99%